Implementation and Application of a Root Growth Module in HYDRUS. Issue 1 (7th September 2017) - Hartmann, Anne; Šimůnek, Jiří; Aidoo, Moses Kwame; Seidel, Sabine J.; Lazarovitch, Naftali
Abstract : Core Ideas: A HYDRUS module was implemented to model root growth as a function of environmental stresses. Simulations were compared with experimental data for temperature stress effects on root growth. Temperature‐dependent root growth parameters were fitted to experimental data using DREAM. A sensitivity analysis of model parameters revealed key parameters of the modeling approach. A root growth module was adapted and implemented into the HYDRUS software packages to model root growth as a function of different environmental stresses. The model assumes that various environmental factors, as well as soil hydraulic properties, can influence root development under suboptimal conditions. The implementation of growth and stress functions in the HYDRUS software opens the opportunity to derive parameters of these functions from laboratory or field experimental data using inverse modeling. One of the most important environmental factors influencing root growth is soil temperature. The effects of temperature in the root growth module was the first part of the newly developed HYDRUS add‐on to be validated by comparing modeling results with measured rooting depths in an aeroponic experimental system with bell pepper ( Capsicum annuum L.). The experiment was conducted at root zone temperatures of 7, 17, and 27°C. Inverse optimization was used to estimate a single set of parameters that was found to well reproduce measured time series of rooting depths for all temperature treatments. A sensitivity analysis showed that parameters such as the maximum rooting depth and cardinal temperatures had only a small impact on the model output and can thus be specified using values from the literature without significantly increasing prediction uncertainties. On the other hand, parameters that define the growth rate or the shape of the temperature stress function had a high influence. The root growth module that considers temperature stress only slightly increased the complexity of the standard HYDRUS models.